Recurrent Intracerebral Hemorrhage after Exercise in a Young Patient Presenting with Sporadic Cerebral Amyloid Angiopathy in a Young Patient - Malik, Muhammad Taimur; Myers, Corey; Kazmi, Syed Jaffar; Zand, Ramin (Journal of vascular and interventional neurology, 2017)
Cerebral Amyloid Angiopathy (CAA) is one of the significant causes of lobar intracerebral hemorrhage (ICH) mainly among elderly people. Sporadic cases of CAA have been linked to genetic polymorphisms with an increased risk of disease, an earlier presentation, and an accelerated pathology [1]. Here, we present a patient with no significant risk factors who had a recurrent intracerebral hemorrhage secondary to CAA probably induced by exercise.